The Effectiveness of Active Learning Strategies in Acquiring Scientific Concepts in Fifth Grade Students in Geography Selected Research from the Master's Thesis. - مصطفی, سەناریا ابراهیم مصطفی; ئازاد, آ.م.د. کوردستان محمد ئازاد (Sulaimani Journal for Humanities, 2025)
The aim of this research is to determine( the effects of active learning strategies upon learning scientific term for the 5th grade student and their desire toward social/ geographical subject). In this research, experiential method has been applied to reach the objectives of the research, the population is composed of the students of 5th grade in a basic schools of sulaymaniyah city, The sample consists of 42 students from Daban basic school, which is a part of the east educational administration for 2024-2025. Which is divided to two classes: experiential andcontrolled. Equivalence has been noticed between (د،ج ) classes in the variables of age, IQ levels, their final grade from last year in social subjects, academic levels of their parent, pre-exam for students previous informations in geography subject and assesing their desire for geography subject before examination. It came into view that they are equivalent in those variables that has been mentioned before, hence the researchers suggested new lecturing strategies to be used for social program subjects.and to give awareness to social subjects teachers That students are learning better and are more active in class by using active learning strategies. In this research two apparatus has been prepared, one to acquire the terms, which was composed of 18 units, validity and the constant has been found, then it has been referred to a group of 15 professors of psychological lecturers. The second one was for the students direction for geography subject, which was composed of 25 units, validity and constant has been found,then it has been referred to a group of 17 professors of psychological lecturers. Coefficient of different statistics has been used to determine the median and standard deviation of the students Answers.
Keywords: Influence; Strategy; Active Learning; Concepts